Phylogenetics, classification, and biogeography of the Neotropical forest lizards (Squamata, Diploglossidae) - Schools, Molly; Hedges, S. Blair (Zootaxa, 2021)
Lizards of the family Diploglossidae occur in moist, tropical forests of Middle America, South America, and Caribbean islands. Our analyses based on new molecular and morphological data indicate that the widely distributed genera Celestus Gray, 1839 and Diploglossus Wiegmann, 1834 are paraphyletic. We restrict the former to Caribbean islands and the latter to South America and Caribbean islands. We assign species in Middle America, formerly placed in Celestus and Diploglossus, to Advenus gen. nov., Mesoamericus gen. nov., and Siderolamprus Cope, 1861. We assign species on Caribbean islands, formerly placed in Celestus, to Caribicus gen. nov., Comptus gen. nov., Celestus, Panolopus Cope, 1862, Sauresia Gray, 1852, and Wetmorena Cochran, 1927. Our phylogenetic tree supports three major clades in the family: Celestinae subfam. nov. (Advenus gen. nov., Caribicus gen. nov., Comptus gen. nov., Celestus, Panolopus, Sauresia, and Wetmorena), Diploglossinae (Diploglossus and Ophiodes Wagler, 1828), and Siderolamprinae subfam. nov. (Mesoamericus gen. nov. and Siderolamprus). Our timetree indicates that the diploglossid lineage originated in the early Cenozoic and established three major centers of diversification in the Americas: Middle America (siderolamprines and one celestine), South America (diploglossines), and Caribbean islands (celestines and diploglossines). The majority of threatened species are on Caribbean islands, with the major threats being deforestation and predation by the introduced mongoose. Molecular and morphological data indicate that there are many undescribed species in this family of lizards.